Carcinoma Lung Presenting with Skeletal Muscle Metastasis: Case Report with Review of Literature - Lalchandani, Ankit; Shukla, Yogeshwar; Parwez, Mohammad Masoom; Kumar, Vinay (The Surgery Journal, 2021)
Lung cancers usually present very late with distant metastasis, thereby carrying a poor prognosis. Metastasis at unusual sites such as extremity musculature does create a diagnostic challenge. This leads to delay in diagnosis and treatment initiation and further worsens the prognosis of the patient. Not many cases have been reported as of now and no standard guidelines are available regarding clinical approach in such cases. We have presented one of such cases to emphasize on importance of early detection and differentiation of such lesions from primary soft tissue malignancies.
Keywords: lung cancer; skeletal muscle metastasis; soft tissue metastasis; carcinoma lung